An evaluation of energy-environment-economic efficiency for EU, APEC and ASEAN countries - Soushi Suzuki; Peter Nijkamp (European Regional Science Association (ERSA), 2015)
This paper aims to offer an advanced assessment methodology for sustainable national energy-environment-economic efficiency strategies, based on an extended Data Envelopment Analysis (DEA) in which distinct countries are regarded as Decision Making Units (DMUs). The aim is to show how much various countries can improve their combined efficiency profile. Standard DEA models use a uniform input reduction or a uniform output increase in their improvement projections. The development of novel efficiency-improvement solutions based on DEA has greatly progressed in recent years. A recent example is the Distance Friction Minimisation (DFM) method, which aims to generate an original contribution to efficiency-enhancement strategies by deploying a weighted projection function, while it may address both input reduction and output increase as a strategy of a DMU. To design a feasible improvement strategy for low-efficiency DMUs, we develop a Target-Oriented (TO) DFM model that allows for less ambitious reference points that remain below the efficiency frontier. The TO-DFM model calculates then a Target-Efficiency Score (TES) for inefficient DMUs. This model is able to compute an input reduction value and an output increase value in order to achieve this TES. However, in many real-world cases the input factor may not be immediately flexible or adjustable, due to indivisibility (or lumpiness) of the input factor. Usually, a DEA model does not include such a non-controllable or a fixed factor. In this study, we aim to integrate the TO-DFM model with a fixed factor (FF) model in order to cope with realistic circumstances in our search for an efficiency improvement projection in combined energy-environment-economic strategies of individual nations. The present paper aims to offer an original contribution to efficiency enhancement in national sustainability strategies by means of the above described DEA approach. After the description of the methodology, a complementary Super-efficiency (SE) approach to DEA is used in our comparative study on the efficiency assessment of energy-environment-economic targets for the EU, APEC and ASEAN (A&A) countries, using appropriate data sets ranging from the years 2003 to 2012. In the present study, we consider two inputs (primary energy consumption and population) and two outputs (CO2 and GDP), including a fixed input factor, namely the ?population? production factor that cannot be flexibly adjusted. On the basis of our DEA analysis results, it appears that EU countries exhibit generally a higher efficiency than A&A countries. In particular, it turns out that Cyprus, Luxembourg and Ireland may be seen as super-efficient countries in the EU, and Brunei as a high performance country in A&A. The above-mentioned TO-DFM-FF projection model is used to address realistic circumstances and requirements in an operational sustainability strategy for efficiency improvement in inefficient countries in the A&A region.
Keywords: C00; Q48; 330; dea; fixed factor; energy-environment-economic efficiency; eu; apec; asean